COVID-19 and vitamin D- a systematic review - Jordan Taja; Siuka Darko; Rotovnik Nada Kozjek; Pfeifer Marija (Sciendo, 2022)
The COVID-19 pandemic has strongly affected global healthcare systems. Prior epidemiological studies on different infectious diseases have shown a strong correlation between serum vitamin D levels and the incidence of certain infectious diseases. Vitamin D has an important immunomodulatory effect on innate immunity and exhibits several other mechanisms in the pathogenesis of the cytokine storm, which is one of the main contributing factors to fatality in COVID-19 patients.